Influence of short-term hypoxic exposure on spatial learning and memory function and brain-derived neurotrophic factor in rats—A practical implication to human's lost way - Kiuchi, Masataka; Uno, Tadashi; Hasegawa, Tatsuya; Koyama, Katsuhiro; Horiuchi, Masahiro (Frontiers in Behavioral Neuroscience, 2024)
The present study aimed to investigate the effects of a short period of normobaric hypoxic exposure on spatial learning and memory, and brain-derived neurotrophic factor (BDNF) levels in the rat hippocampus. Hypoxic conditions were set at 12.5% O2. We compared all variables between normoxic trials (Norm), after 24 h (Hypo-24 h), and after 72 h of hypoxic exposure (Hypo-72 h). Spatial learning and memory were evaluated by using a water-finding task in an open field. Time to find water drinking fountains was significantly extended in Hypo 24 h (36.2±21.9 s) compared to those in Norm (17.9±12.8 s) (P<0.05), whereas no statistical differences between Norm and Hypo-72 h (22.7±12.3 s). Moreover, hippocampal BDNF level in Hypo-24 h was significantly lower compared to Norm (189.4±28.4 vs. 224.9±47.7 ng/g wet tissue, P<0.05), whereas no statistically differences in those between Norm and Hypo-72 h (228.1±39.8 ng/g wet tissue). No significant differences in the changes in corticosterone and adrenocorticotropic hormone levels were observed across the three conditions. When data from Hypo-24 h and Hypo-72 h of hypoxia were pooled, there was a marginal negative relationship between the time to find drinking fountains and BDNF (P<0.1), and was a significant negative relationship between the locomotor activities and BDNF (P<0.05). These results suggest that acute hypoxic exposure (24 h) may impair spatial learning and memory; however, it recovered after 72 h of hypoxic exposure. These changes in spatial learning and memory may be associated with changes in the hippocampal BDNF levels in rats.